2015
DOI: 10.4049/jimmunol.1401443
|View full text |Cite
|
Sign up to set email alerts
|

Sterile DJH Rearrangements Reveal that Distance Between Gene Segments on the Human Ig H Chain Locus Influences Their Ability To Rearrange

Abstract: Rearrangement of the Ig locus occurs in two steps. First, a JH gene is rearranged to a D gene followed by a VH gene rearranging to the DJH rearrangement. By next generation sequencing, we analyzed 9969 unique DJH rearrangements and 5919 unique VHDJH rearrangements obtained from peripheral blood B cells from 110 healthy adult donors. We found that DJH rearrangements and nonproductive VHDJH rearrangements share many features but differ significantly in their use of D genes and propensity for somatic hypermutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 39 publications
3
13
0
Order By: Relevance
“…The size of the datasets enabled us to focus on non-productive sequence data, allowing us to exclude the possibility that observed biases were an outcome of selection acting upon transcribed genes. Significant differences in gene usage between productive and non-productive sequences were seen for some but not all D genes, confirming recent reports (26). These differences between IGHD genes may in part be explained by their varying utilization frequencies.…”
Section: Discussionsupporting
confidence: 90%
“…The size of the datasets enabled us to focus on non-productive sequence data, allowing us to exclude the possibility that observed biases were an outcome of selection acting upon transcribed genes. Significant differences in gene usage between productive and non-productive sequences were seen for some but not all D genes, confirming recent reports (26). These differences between IGHD genes may in part be explained by their varying utilization frequencies.…”
Section: Discussionsupporting
confidence: 90%
“…Previous research has shown that the broad differences in gene usage are determined by the structure of these loci, such as gene copy number variation and proximity of V gene segments to the D and J loci5. However, the similarity of twins' CD4 + and CD8 + repertoires, as well as the similarity of the non-productive B-cell repertoires in twin-pairs, shows that these broadly defined patterns can be altered within an individual to create a unique repertoire.…”
Section: Discussionmentioning
confidence: 99%
“…Although the process of selecting gene segments for recombination is largely random, some are used more often than others. Studies have shown that overall biases in gene segment usage are the product of a variety of mechanisms, including a preferred recombination between certain V and (D)J segments2; receptor selection based on binding affinity for different major histocompatibility complexes (MHCs; for T-cell receptor (TCR) rearrangements)34; and bias based on the distance between V, D and J segments (for immunoglobulin (Ig) rearrangements)5. However, detailed studies using monozygotic (MZ) twins have shown that additional unidentified genetically encoded mechanisms must also contribute to the relative usage of individual gene segments678910.…”
mentioning
confidence: 99%
“…The method has been published in Barington et al : reads were qualified by the presence of primer and MID sequences and identical sequences (at least 1 forward and 1 reverse) were clustered. Clusters from the same PCR could be identified based on the primers and MIDs and were analyzed separately in the following: Clusters were evaluated by a numerical programming algorithm designed by the authors (details available from the corresponding author).…”
Section: Methodsmentioning
confidence: 99%